Low Blood Pressure at Presentation and its Adverse Outcomes in Acute Stroke - Ayesha Shahjahan, Syed Irfan Ahmed, Syed Muhammad Saqib, Saad Bin Ejaz (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Most patients with acute ischemic stroke (AIS) have elevated blood pressure (BP) at presentation, which often declines spontaneously in the following days. Objectives: The main objective of the study is to find the Low blood pressure at presentation and its adverse outcomes in acute stroke. Material and methods: This cross sectional study was conducted in Akbar Niazi Teaching Hospital, Barakahu, Islamabad during July 2022 till October 2022. The data was collected with the permission of ethical committee of hospital. The data was collected from those patients who fulfill the inclusion criteria. We collect all the data related to age, sex, history of diseases, risk factors, baseline values and stroke history. All suspected strokes who presented to the ED within 24 h of onset of first symptoms were included in this prospective study Results: In our study total 100 patients were enrolled mean age was 47.7± 10 years with minimum age of 18 years and maximum age of 65 years. Lesser patients belong to younger age group (18 years to 40 years) i.e. 54 while 46 belonged to elder age group i.e. 41 year to 65 years 24.1 % and 75.9% respectively. Out of which 62 were male and 38 were female. Practical implication: Hypotension and hypertension both are inter connected and treated simultaneously. Conclusion: It is concluded that hypotension were the commonest non communicable diseases (cardiovascular) risk factors in known hypertensive patients. Low presenting BP, both SBP and DBP, are associated with poor outcome after acute stroke, even after taking account of these patients. Keywords: Hypotension, Blood pressure, Stroke, Hypertension, Outcomes